Perlindungan Hukum Bagi Konsumen Dalam Jual Beli Secara Online - Budi Bahreysi (Universitas Muhammadiyah Sumatera Utara, 2018)
Buying and selling is a legal act related to the transfer of ownership rights to goods that are objects of sale and purchase. In general, buying and selling activities are subject to the legal provisions stipulated in Chapter V of the Civil Code (Civil Code). In Chapter V of the Civil Code it is regulated about the notion of buying and selling, the limits of buying and selling to the obligation of the seller and the buyer in a sale and purchase transaction that he has done. At this time the development of the era is increasingly fast and complex, very influential on the needs of every human being. This progress was marked by developments in the field of science and technology that made it easier for humans to communicate remotely. And for these consequences many legal events were born as a form of improvement over the shortcomings that had been a barrier for everyone. Buying and selling now no longer need to be done face to face, but can be done remotely without having to see without even knowing each other before.